Analysis Of Weather Conditions and Hydrodynamics in Taman Nasional Bunaken - Molle, Ben Arther; Schaduw, Joshian Nicolas William; Sumilat, Deiske Adeliene; Rondonuwu, Ari Berty; Luasunaung, Alfret; Warouw, Veibe (Jurnal Ilmiah Platax, 2022)
Taman Nasional Bunaken (TNB) is located in North Sulawesi Province, Republic of Indonesia. TNB offers an exploration experience of marine tourism such as snorkeling and diving. This study was conducted to determine the statistics and correlation of weather parameters on hydrodynamics in the waters of the small island of TNB. This information can be used by marine tourism users. The weather data studied are wind direction and speed. The hydrodynamic conditions studied were wave height and ocean currents. Respondent surveys were also conducted on tourist users at the research sites. The wind direction for the period January - April is dominant from the Northeast, May - September is dominant from the East to the South, October tends to be evenly distributed from the East to the West, and November - December is dominant from the West. Significant wind speeds that occur in January, February, and March range from 18 – 36 knots. The average wave height shows a significant value in January – March, tends to be lower in April – June, fluctuates in July – November, and increases again in December. The maximum current velocity at a sea depth of 16.5 m is stronger than the maximum speed at a depth of 0.5 m and 8.0 m in January – April, and May August. The correlation value of wind speed and sea wave height is significant at 0.96 and the correlation between wind speed and the current speed is 0.74. These results indicate that there is a strong -very strong relationship between parameters. The survey results show that wind speed, wave height, and ocean currents have the same pattern. January, February, November, and December are the months of extreme or bad weather and hydrodynamic conditions.Keywords: Taman Nasional Bunaken, Weather, Hydrodynamics, CorrelationAbstrakTaman Nasional Bunaken (TNB) terletak di Provinsi Sulawesi Utara, Negara Republik Indonesia. TNB  menawarkan pengalaman eksplorasi suasana wisata bahari seperti snorkling dan diving. Penelitian ini dilakukan untuk mengetahui statistik dan korelasi parameter cuaca terhadap hidrodinamika di perairan pulau kecil TNB. Informasi tersebut dapat digunakan oleh pengguna wisata bahari. Data cuaca yang diteliti adalah arah dan kecepatan angin. Kondisi hidrodinamika yang diteliti ialah tinggi gelombang dan arus laut. Survei responden juga dilakukan kepada pengguna wisata di lokasi penelitian. Arah angin periode Bulan Januari - April dominan dari arah Timur Laut, Bulan Mei – September dominan dari arah Timur hingga Selatan, Bulan Oktober cenderung merata dari arah Timur hingga Barat dan Bulan November – Desember dominan dari arah Barat. Kecepatan angin signifikan terjadi pada bulan Januari, Februari, dan Maret berkisar antara 18 – 36 Knot. Rata-rata tinggi gelombang menunjukan nilai signifikan pada bulan Januari – Maret, cenderung merendah pada bulan April – Juni, berfluktuasi pada bulan Juli – November dan meningkat kembali di bulan Desember. Kecepatan maksimum arus laut di kedalaman 16.5 m lebih kuat jika dibandingkan kecepatan maksimum di kedalaman 0.5 m dan 8.0 m pada bulan Januari – April serta bulan Mei – Agustus. Nilai korelasi kecepatan angin dan tinggi gelombang laut signifikan sebesar 0.96 serta korelasi kecepatan angin dan kecepatan arus sebesar 0.74. Hasil tersebut menunjukkan antar parameter memiliki hubungan yang kuat - sangat kuat. Hasil survei menunjukan kecepatan angin, tinggi gelombang dan arus laut mempunyai pola yang sama. Bulan Januari, Februari, November, dan Desember merupakan bulan-bulan terjadinya kondisi cuaca serta hidrodinamika ekstrem atau buruk.Kata kunci: Taman Nasional Bunaken, Cuaca, Hidrodinamika, Korelasi